Cross‐taxon congruence in lake plankton largely independent of environmental gradients. Issue 10 (1st October 2014) - Özkan, Korhan; Jeppesen, Erik; Davidson, Thomas A.; Søndergaard, Martin; Lauridsen, Torben L.; Bjerring, Rikke; Johansson, Liselotte S.; Svenning, Jens-Christian
Abstract : Groups of organisms often have congruent patterns of diversity or community structure due to similar environmental requirements. However, ecological interactions across trophic levels may also promote congruence independent of environmental drivers through selective predation, niche partitioning, or facilitation. We examined congruence between phytoplankton and zooplankton communities using 20 years of monitoring data from 17 Danish lakes, most of which were subject to external nutrient loading reduction after a period of eutrophication. Linear mixed effect models and partial Mantel tests were used to elucidate the extent to which congruence in genus richness and composition was driven by environmental factors. Congruence not explained by environmental controls might indicate ecological interactions across trophic levels of lake plankton. Genus richness and composition of phyto‐ and zooplankton were significantly congruent. Environmental factors had limited power to explain the genus richness of phyto‐ and zooplankton ( R 2 : 6% and 12%, respectively). Including richness of the reciprocal group among the predictors markedly improved each respective model and explanatory power ( R 2 : 11% and 17%, respectively). Similarly, a large proportion of the congruence in genus composition was independent of environmental dissimilarity (Mantel r : 0.29 and partial Mantel r after accounting for environmental control: 0.17). The strength of the congruence varied among different groups of phyto‐ and zooplankton, likely reflecting that the different zooplankton groups differ in their grazing size spectra and thus in the strength of their coupling with the phytoplankton assemblages. Remarkably, congruence with phytoplankton was strongest for the smallest group of zooplankton, rotifers, which graze on a limited size spectrum of phytoplankton. Moreover, congruence was stronger in low‐nutrient lakes, suggesting that the strength of the interactions between the two groups weakens with eutrophication. This is likely due to changes in trophic dynamics, where enhanced fish predation on large‐bodied zooplankton with increasing nutrient levels results in reduced zooplankton grazing control of phytoplankton assemblages.